Isolation and selection of indole acetic acid (IAA) producing bacteria from cultivated soil of Vietnamese ginseng in Quang Nam - Bao Tram, Tran (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Among 31 bacterial strains isolated from cultivated soil of Vietnamese ginseng in Quang Nam province, the P6 was the highest potential of IAA biosynthesis strain. The analyses of morphological and biochemical characteristics as well as 16S rRNA gene sequencing identified that the P6 strain belongs to Kluyvera cryocrescens species (99.93% similarity). The results of studying on culture conditions of the strain K. cryocrescens showed that King’s B medium with nitrogen source as peptone and KNO 3 (0,5% w/v), added 0,1% tryptophan (w/v) at 30 o C gave the highest IAA content (97,7 µg/ml) after 4 days of cultivation. The effect of crude IAA formed in the culture liquid of K.cryocrescens on germination rate of cucumber seeds and growth of cucumber trees indicated that: germination rate of the block treated with IAA liquid is 93.3% higher than that of the control block of 80%. After 10 days of sowing, the trees of the experimental  block had rapid and even growth, the length of their stem and roots, the weight of their stem and leaves as well as their root number all developed better than the control block